2004
DOI: 10.1038/ng1368
|View full text |Cite
|
Sign up to set email alerts
|

The mouse X chromosome is enriched for sex-biased genes not subject to selection by meiotic sex chromosome inactivation

Abstract: Sex chromosomes are subject to sex-specific selective evolutionary forces 1,2 . One model predicts that genes with sexbiased expression should be enriched on the X chromosome 2-5 . In agreement with Rice's hypothesis 3 , spermatogonial genes are over-represented on the X chromosome of mice 6 and sex-and reproduction-related genes are over-represented on the human X chromosome 7,8 . Male-biased genes are under-represented on the X chromosome in worms and flies 9-11 , however. Here we show that mouse spermatogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

34
320
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(355 citation statements)
references
References 31 publications
34
320
0
1
Order By: Relevance
“…Our data strongly support the idea that the X chromosome has an unusual distribution of genes with male-biased expression 4,5,[16][17][18] . Although there is compelling evidence that precocious X chromosome inactivation occurs in at least some species, and that this may contribute to the reduced density of genes with male-biased expression on X chromosomes 4,5 , our data indicate that this is not a major contributor to the pattern in the Drosophila genus.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Our data strongly support the idea that the X chromosome has an unusual distribution of genes with male-biased expression 4,5,[16][17][18] . Although there is compelling evidence that precocious X chromosome inactivation occurs in at least some species, and that this may contribute to the reduced density of genes with male-biased expression on X chromosomes 4,5 , our data indicate that this is not a major contributor to the pattern in the Drosophila genus.…”
supporting
confidence: 87%
“…We observe the same under-representation on the neo-X of D. pseudoobscura. It has been suggested that precocious meiotic silencing of the X chromosome accounts for reduced X chromosome male-biased expression in nematodes 4 , mammals 5 and Drosophila 6 . We show that X chromosome genes with male-biased expression are under-represented in somatic cells and in mitotic male germ cells.…”
mentioning
confidence: 99%
“…Profiles of genome expression indicate enrichment of female-limited genes on the X chromosome of D. melanogaster [66], Drosophila simulans [67] and the mouse [68] and of malelimited genes on the Z chromosome of the chicken [65]. However, genes with male-biased expression are underrepresented on the X chromosomes of Drosophila and Caenorhabditis elegans [66,67,69] and on the Z chromosome of the chicken [65].…”
Section: Pr Ospects and Overviews J E Ironsidementioning
confidence: 99%
“…When 36 germ cell-specific genes were identified from mouse spermatogonia in a systematic genomic screen (Table 1), nearly one-third of these genes were X-linked, demonstrating that early spermatogenesis genes are enriched on the X chromosome in mouse (Wang et al 2001). [Such enrichment is also substantiated by genomic studies of the mouse Spo11 mutant and human germ cell-restricted genes (Khil et al 2004, Koslowski et al 2006]. To date, 13 out of these 36 genes (Sycp1,Sycp2,Sycp3,Sall4,Figla,Stra8,Tex14,Ddx4,Rnf17,Piwil2,Dazl,Tdrd1, and Taf 7l) have been characterized by targeted inactivation in mice (Table 1).…”
Section: Enrichment Of Early Spermatogenesis Genes On the Mammalian Xmentioning
confidence: 98%
“…Topoisomerase SPO11 is required for homologous recombination and its loss causes meiotic arrest prior to the pachytene stage in mouse (Baudat et al 2000, Romanienko & CameriniOtero 2000. Expression profiling of Spo11-deficient testes showed that genes expressed before the Spo11 block are enriched on the X chromosome, whereas those expressed after the block are under-represented (Khil et al 2004). It has been hypothesized that male beneficial genes (for example, genes expressed in early spermatogenesis) tend to accumulate on the X chromosome during evolution because of its hemizygosity in males (Rice 1984).…”
mentioning
confidence: 99%